Gender differences in self-risk evaluation: Evidence from the Renrendai online lending platform - Xun Li; Yuxin Deng; Shanlin Li (Journal of Applied Economics, 2020)
Risk-related gender differences such as risk perception and risk aver - sion are widely discussed, whereas gender differences in self-risk evaluations are unknown. Using a sample of more than 310,000 individual loan applications from the Renrendai online lending plat - form, this study uses a hedonic model to examine gender differences in self-risk evaluations. We find that males are more likely than females to offer lower interest rate premiums when they have favor - able attributes, such as larger loans, higher credit ratings, married status, and income level, and females tend to offer lower interest rate premiums when they have unfavorable attributes, such as longer- term loans. We conclude that males seek benefits and females avoid disadvantages when evaluating their own risk, which is supported by economic, biological and psychological research. Our findings fill this gap on gender differences in risk-related behaviors.
Keywords: 330; Self-risk evaluation; P2P; gender difference